PHARMACEUTICAL INCOMPATIBILITES: A REVIEW - Begum, S. Gousia; Reddy, Y. Dastagiri; Divya, B. Sri; Komali, P.Komali; Sushmitha, K.; Ruksar, S. (Asian Journal of Pharmaceutical Research and Development, 2018)
Incompatibility is defined as a change resulting and an undesirable product is formed, which may affect the safety, efficacy, appearance and stability of the pharmaceutical product. It is of three types. It includes physical, chemical and therapeutic incompatibilities. The below described article gives the detailed information about the types, causes and how to overcome these types of incompatibilities. The occurrence of chemical incompatibilities can be overcome by two methods which include method A&B.